Development of a Research-Based Digital Teaching Supplement on Heavy Metal Pollution to Equip Junior High School Students with Digital Literacy Skills - Laut Padi Sih Sesami; Dewi Mustikaningtyas (Universitas Negeri Semarang, 2025)
Heavy metal pollution is an environmental problem that directly impacts human health and the sustainability of aquatic ecosystems. Research indicates that the issue of heavy metal pollution can be used as a contextual learning resource to foster students’ digital literacy skills and environmental awareness. Preliminary observations at SMP Negeri 1 Boja revealed that students’ digital literacy skills remain relatively low, indicating the need for innovative learning resources to enhance these competencies. This study aims to develop a research-based digital teaching supplement on heavy metal pollution to equip junior high school students with digital literacy skills. The research employed the ADDIE model, comprising the stages of analysis, design, development, implementation, and evaluation. The study involved eighth-grade students at SMP Negeri 1 Boja during the 2024/2025 academic year. Data analysis used descriptive statistics to assess validity and practicality, as well as percentage achievement analysis to evaluate students’ digital literacy. The results show that: (1) material expert validation scored 91.54% (very feasible) and media expert validation scored 93.07% (very feasible), (2) student responses indicated a practicality score of 93.06% (very practical), and (3) students’ digital literacy averaged 85.74% (very good) across the five aspects: accessing (90.00%), selecting (83.97%), understanding (90.15%), evaluating (80.44%), and producing (84.12%). These findings demonstrate that the developed research-based digital teaching supplement is highly feasible, highly practical, and effective in equipping students with strong digital literacy skills.